Analysis of the Intentionality and usability of business intelligence in the context of Industry 5.0 and its impact on Colombian international trade - Jaime Alfonso Arciniegas-Ortiz; Leonardo Juan Ramírez-López (Dyna)
In Colombia, integrating educational technology (EdTech) is crucial for enhancing educational quality and efficiency, especially in the post-pandemic context. Researchers [1] highlight the significant role of online platforms, yet challenges persist, such as the need for robust technological infrastructure and comprehensive teacher training. With 55.3% of universities adopting these platforms, reliance on external technologies and insufficient investment in local EdTech hinder innovation, as noted by [2]. [3] advocate for investing in local EdTech to improve education and stimulate economic development. In the industrial sector, under Industry 5.0, Business Intelligence (BI) is vital for boosting international trade through data analysis and informed decision-making. [4] emphasizes tools like Power BI for competitiveness, while DANE data indicates that 40.1% of companies outsource technology management, highlighting the need to develop local expertise to ensure sustainable growth and align BI with national economic goals.